2001
DOI: 10.1016/s1010-7940(01)00841-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase responses following minimal access and conventional thoracic surgery

Abstract: VATS pulmonary lobectomy is associated with reduced peri-operative changes in acute phase responses. This finding may have implications for peri-operative tumour immuno-surveillance in lung cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
145
0
10

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(165 citation statements)
references
References 19 publications
10
145
0
10
Order By: Relevance
“…VATS or thoracotomy. Previous studies [26][27][28] comparing serum IL-6 levels in VATS with those in conventional thoracotomy demonstrated that the serum IL-6 levels were significantly lower in VATS than in conventional thoracotomy. Our results for all patients or for patients with confirmed pathological stage I A + I B were consistent with those in previously published reports.…”
Section: Discussionmentioning
confidence: 98%
“…VATS or thoracotomy. Previous studies [26][27][28] comparing serum IL-6 levels in VATS with those in conventional thoracotomy demonstrated that the serum IL-6 levels were significantly lower in VATS than in conventional thoracotomy. Our results for all patients or for patients with confirmed pathological stage I A + I B were consistent with those in previously published reports.…”
Section: Discussionmentioning
confidence: 98%
“…The minimal invasiveness of VATS lobectomy may reduce the immunosuppressive cytokine effect (36). Craig et al (37) demonstrated that VATS pulmonary lobectomy is associated with reduced peri-operative changes in acute phase responses. This finding may have implications for peri-operative tumor immuno-surveillance in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies [79,80] reported information on outcomes of interest and found no substantial differences between the groups, except for fewer air leaks found in the study by Kirby et al [78].…”
Section: Vats Major Pulmonary Resectionsmentioning
confidence: 90%
“…Nevertheless, these presumed advantages over open surgery have neither been clearly assessed nor demonstrated in a systematic review of the evidence from randomized trials, rendering it impossible to make recommendations for best practice or to provide guidance for wider application of this minimally invasive technique [77][78][79][80].…”
Section: Vats Major Pulmonary Resectionsmentioning
confidence: 99%
See 1 more Smart Citation